Fabrication, mechanical, and electromagnetic studies of cobalt ferrite based‐epoxy nanocomposites. Issue 1 (9th October 2020) - Yang, Yong; Ali, Farman; Said, Amir; Ali, Nisar; Ahmad, Sohrab; Raziq, Fazal; Khan, Sajid
Abstract: Controlling the interface, contact of organic‐inorganic materials is necessary for the preparation of high‐performance hybrid nanocomposites. Herein, the cobalt ferrite (CoFe2 O4 ) nanofiller was synthesized via coprecipitation route by the reaction of Fe2 (SO4 )3, CoSO4, and triethylene glycol. The obtained CoFe2 O4 nanoparticles were thermally treated at 600°C for 5 hours. As prepared, the CoFe2 O4 nanoparticles were surface functionalized with 3‐(triethoxysilyl) propylamine (APTES). The modified CoFe2 O4 nanoparticles were used as reinforcement during the fabrication of epoxy‐based CoFe2 O4 nanocomposite. The synthesized nanofillers and nanocomposites were structurally examined by Fourier transform infrared, X‐ray diffraction analysis, scanning electron microscopy, and thermogravimetric analysis. The effect of nanofiller on surface resistivity, electrical conductivity, and mechanical performance was also investigated. The surface resistivity of EP‐CoFe2 O4 nanocomposite decreases with increasing loading concentration of CoFe2 O4, while thermal degradation temperatures are improved by 90 K (12.7%) compared to neat EP‐polymer. The mechanical properties, that is, stress‐strain and Young's modulus show an increase of about 60% and 35%, respectively, at 5 wt% CoFe2 O4 content. The incredible improvement in the electrical conductivity, mechanical, and thermal stability of EP‐CoFe2 O4 up to 5%wt. CoFe2 O4 contents are attained due to smaller size and well dispersion of nanofillers in the polymeric matrix. These simultaneous enhancements in properties intend that the EP‐CoFe2 O4 nanocomposites can be useful as protective coatings and corrosion‐resistant for a variety of applications Abstract :